2018
DOI: 10.3389/fcimb.2018.00089
|View full text |Cite
|
Sign up to set email alerts
|

Population Genomics of Francisella tularensis subsp. holarctica and its Implication on the Eco-Epidemiology of Tularemia in Switzerland

Abstract: Whole genome sequencing (WGS) methods provide new possibilities in the field of molecular epidemiology. This is particularly true for monomorphic organisms where the discriminatory power of traditional methods (e.g., restriction enzyme length polymorphism typing, multi locus sequence typing etc.) is inadequate to elucidate complex disease transmission patterns, as well as resolving the phylogeny at high resolution on a micro-geographic scale. In this study, we present insights into the population structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 54 publications
4
46
0
1
Order By: Relevance
“…flies and mosquitoes) also play an important role but, at least in France, this role in tularemia transmission has been poorly studied. A recent study in Switzerland, where ticks were found to be the main cause of infection in humans (Lyko and Chuard, 2013), suggested that strains of clade B.45 were better adapted than other clades to arthropods vectors, as clade B.46 and the newly identified B.11 subclades were isolated only in humans and mammals (Wittwer et al, 2018). However, in France, tick bites represent only around 10% of tularemia cases (Maurin et al, 2011) andMichelet et al (2014) suggested that the risk of acquiring tularemia from ticks -Ixodes ricinus at least -was negligible.…”
Section: Geographic Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…flies and mosquitoes) also play an important role but, at least in France, this role in tularemia transmission has been poorly studied. A recent study in Switzerland, where ticks were found to be the main cause of infection in humans (Lyko and Chuard, 2013), suggested that strains of clade B.45 were better adapted than other clades to arthropods vectors, as clade B.46 and the newly identified B.11 subclades were isolated only in humans and mammals (Wittwer et al, 2018). However, in France, tick bites represent only around 10% of tularemia cases (Maurin et al, 2011) andMichelet et al (2014) suggested that the risk of acquiring tularemia from ticks -Ixodes ricinus at least -was negligible.…”
Section: Geographic Distributionmentioning
confidence: 99%
“…Clade B.6 is found in Western Europe and North America, whereas clade B.12 has been isolated mainly in Eastern Europe, and groups together erythromycin-resistant strains (Vogler et al, 2009). In Germany, Switzerland, Sweden, Norway and Finland, both of these major clades have been detected (Karlsson et al, 2013;Müller et al, 2013;Origgi et al, 2014;Afset et al, 2015;Sissonen et al, 2015;Wittwer et al, 2018). Clade B.16 correlates with biovar japonica, isolated in Japan and recently in Turkey (Ulu-Kilic et al, 2013), China (Wang et al, 2014), and Australia (Eden et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Catalase and oxidase reaction tested negative. ural reservoir and ticks as vectors 10 . The species F. tularensis comprises two subspecies, namely tularensis (Type A strain) and holarctica (Type B strain) 5 .…”
Section: Microbiological Examinationsmentioning
confidence: 99%
“…The incidence of tularemia in humans in Switzerland increased significantly from seven cases in 2004 to 131 cases in 2017 according to the annual case numbers of the Swiss Federal Office for Public Health and is now considered a reemerging disease with an increasing veterinary public health relevance 4,10 . An epidemiological study of 276 human tularemia cases in Switzerland investigated causative risk factors for disease occurrence.…”
Section: Microbiological Examinationsmentioning
confidence: 99%
See 1 more Smart Citation